PKM UMKM Culinary Based on Information Technology: E-Commerce Website Design in Legok Village, Tangerang, Banten - Melissa Fianty; Fahmy Rinanda Saputri; Cynthia Sari Dewi (I-Com: Indonesian Community Journal, 2023)
This Community Partnership Program Activity (PKM) partners with Putri’s Home Cooking, a culinary SME located in Desa Legok, Tangerang, Banten. One crucial aspect of the business is marketing, and the challenges faced by the partner include difficulty in acquiring new customers, the absence of online sales, and the lack of food product labels. The objective of this activity is to utilize technology and science (IPTEK) for culinary SME business strategies to introduce and enhance the ongoing business for the betterment of the community's welfare.The issue confronted by the partner is the limited marketing reach. The solution to this issue involves creating an e-commerce website. The execution method for this activity consists of two phases: firstly, analyzing the partner's situation and conditions, and secondly, preparing the transfer of Appropriate Technology (TTG). The outcomes achieved include product photos for marketing purposes and the design of an e-commerce website, which can be used to market their products, thus helping the partner's culinary SME products from Desa Legok gain wider recognition.